Linking ownership structure with capital structure of rural banks (BPR) in West Java, Indonesia - Muhamad Umar Mai; sudrajat sudrajat; Etti Ernita Sembiring (Postgraduate Program Merdeka University, 2025)
This study examines the relationship between ownership structure and capital structure at rural banks (BPR) in West Java, Indonesia. The ownership structure includes local government ownership, institutional ownership, management ownership, and female shareholding. Meanwhile, capital structure is measured using debt-to-assets ratio (DTAR) and debt-to-equity ratio (DTER). The data in this study was obtained from BPR's financial statements for the period 2016 to 2022. The results of data collection show that there are 218 rural banks in West Java, Indonesia with a total of 1526 BPR-years of observation. Next, the data was analyzed using the Robust standard errors of fixed effects model (Robust FEM). The findings show that local government ownership is positively related to the capital structure of rural banks as measured by DTER. Institutional ownership is positively related to the capital structure of rural banks as measured by DTAR. Meanwhile, women's share ownership is positively related to BPR's capital structure as measured by DTAR and DTER. Although, this study fails to prove the relationship between management ownership and capital structure, however, in general it can be said that ownership structure is related to the capital structure of rural banks in West Java, Indonesia JEL Classification: G21, G34 DOI: https://doi.org/10.26905/afr.v8i1.13114